2021
DOI: 10.3389/fsurg.2021.799607
|View full text |Cite
|
Sign up to set email alerts
|

Scanner-Assisted CO2 Laser Fissurectomy: A Pilot Study

Abstract: Introduction: Surgery for chronic anal fissure is challenging for every proctologist. Solving the pain by guaranteeing rapid and effective healing is the objective, but what is the price to pay today in functional terms? Though this result is nowadays partially achievable through interventions that include the execution of an internal sphincterotomy among the procedures, it is necessary to underline the high rate of patients who can present faecal incontinence. The aim of this study is to explore the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Scanning-aided “free beam” laser surgery is the only technology that enables the surgeon to control the ablation depth and the thermal effect for each scanning passage. Moreover, scanning technology has already been intensively used in many fields of surgery like Gynecology, Colposcopy, Ears-Nose-Throat, Neurosurgery, and General Surgery (i.e., Proctology and Wound Healing) [ 26 , 27 , 28 , 29 , 30 ]. The CO 2 laser can also be delivered using a flexible hollow fiber (i.e., Smartxide2 TRIO System, DEKA, Calenzano, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Scanning-aided “free beam” laser surgery is the only technology that enables the surgeon to control the ablation depth and the thermal effect for each scanning passage. Moreover, scanning technology has already been intensively used in many fields of surgery like Gynecology, Colposcopy, Ears-Nose-Throat, Neurosurgery, and General Surgery (i.e., Proctology and Wound Healing) [ 26 , 27 , 28 , 29 , 30 ]. The CO 2 laser can also be delivered using a flexible hollow fiber (i.e., Smartxide2 TRIO System, DEKA, Calenzano, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that laser exposure can start the regeneration of various tissues because it encourages the development of fibroblasts, increased epidermal growth, collagen formation, vascular structure growth, and total healing. 4,5,21 In a specific study from 2017 conducted on 200 patients suffering from chronic anal fissures, minimally invasive laser electrocoagulation with the help of nitroglycerine or nifedipine was evaluated using anesthesia. The internal sphincter and its margins stay completely unaffected by the electrocoagulation of the fissure.…”
Section: Laser Surgeriesmentioning
confidence: 99%